THE EFFECT OF ECONOMIC GROWTH, INFLATION AND BUSINESS CONFIDENCE INDEX ON UNEMPLOYMENT IN ASEAN-5 - Yusri, Kamilatun Ahsana; Nikensari, Sri Indah; Iranto, Dicky (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
This study aims to see the effect of of economics growth, inflation, and business confidence index in ASEAN-5. The method used in this research is panel data regression method with Vector Error Correction model. This research was conducted in 5 countrys in ASEAN for fiveteen years, 2005-2019. The variables in this study consisted of the economics growth represented by percentage of GDP (X1), inflation represented by consumer price index (X2), business confidence index represented by percentage of business confidence index (X3), and unemployment represented by percentage of unempolyment rate (Y). This data is secondary data obtained through World Bank and Trading Economics in ASEAN-5. The results of this study prove that the variable of economics growth in 1st lag isn’t significant on unemployment, but in 2nd and 3rd lag are significant on unemployment. While the variables of inflation and business confidence index are significant on unemployment.